Analysis of scene-guided camera assistance in transaxillary gasless endoscopic thyroidectomy: a minor improvement in operative technique - Sun, Baihui; Yu, Shitong; Ge, Junna; Zhang, Zhicheng; Chen, Weisheng; Wei, Zhigang; Li, Tingting; Lei, Shangtong (Frontiers in Endocrinology, 2023)
Background Transaxillary gasless endoscopic thyroidectomy (TGET) is a widely performed operation, but its side view angle and instrument interference have caused concerns for most surgical groups. The aim of this study was to introduce scene-guided camera assistance (SGA) and analyze its role in facilitating TGET. Methods We put forward key points for camera holders, including one pivot, two positions, and three planes, and separated TGET operations into five parts. We also established the view angle for each part of the operation for the camera holder to follow. Then, we reviewed 416 patients who underwent TGET with or without SGA and analyzed their demographic characteristics, operative outcomes, pathologic outcomes, and early complications. Results The TGET and TGET-SGA groups were similar in terms of age, sex ratio, height, weight, tumor size, Hashimoto’s thyroiditis ratio, and cN1 ratio. The operation time and postoperative hospital stay were significantly longer in the TGET group than in the TGET-SGA group (114.43 ± 17.20 minutes vs. 101.82 ± 19.39 minutes and 3.16 ± 0.77 days vs. 2.16 ± 0.55 days, respectively, P < 0.001). The account of retrieved lymph nodes was less in the TGET group than in the TGET-SGA group (5.61 ± 4.27 vs. 6.57 ± 4.96, P = 0.038). Conclusions SGA provided guidance for camera holders, and the data showed that it was an improvement for TGET operations.